1999
DOI: 10.1128/mcb.19.4.2724
|View full text |Cite
|
Sign up to set email alerts
|

Human SWI-SNF Component BRG1 Represses Transcription of the c-fos Gene

Abstract: -13 cells potentiated transcriptional activation by the glucocorticoid receptor, which is known to require SWI-SNF function. BRG1 also specifically repressed transcription from a transfected c-fos promoter and correspondingly blocked transcriptional activation of the endogenous c-fos gene. Mutation of lysine residue 798 in the DNA-dependent ATPase domain of BRG1 significantly reduced its ability to repress c-fos transcription. Repression by BRG1 required the cyclic AMP response element of the c-fos promoter bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 81 publications
10
95
1
2
Order By: Relevance
“…Findings from multiple laboratories have suggested that deletion/loss of Brg1 may contribute to the genesis of cancer (Murphy et al, 1999;Lee et al, 2002); however, the underlying mechanism for this process is unclear. The data presented here indicate that loss of Brg1 results in aberrant mitotic progression and provides evidence of genomic instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from multiple laboratories have suggested that deletion/loss of Brg1 may contribute to the genesis of cancer (Murphy et al, 1999;Lee et al, 2002); however, the underlying mechanism for this process is unclear. The data presented here indicate that loss of Brg1 results in aberrant mitotic progression and provides evidence of genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the notion that Brg1 deficiency can be overcome by virtue of additional stochastic events; however, this process was highly sporadic even in the context of immortalized 3T3 populations and selection for Brg1 deletion. Thus, tumor cell lines and potentially other Brg1-deficient cell types, presumably use compensatory mechanisms to bypass the requirement that we observed.Findings from multiple laboratories have suggested that deletion/loss of Brg1 may contribute to the genesis of cancer (Murphy et al, 1999;Lee et al, 2002); however, the underlying mechanism for this process is unclear. The data presented here indicate that loss of Brg1 results in aberrant mitotic progression and provides evidence of genomic instability.…”
mentioning
confidence: 99%
“…Other more distantly related enzymes include human hBrm, Brg1 and the CHD family (CHD1-7). Of note, human hBrm and Brg1 are two candidate tumor suppressor genes that are implicated in repression of E2F target genes and induction of cell differentiation and senescence, through physical and functional interactions with the pRB protein (33,38,56,76,85,104,105,115,124,134,142). Since E2F target genes are incorporated into SAHF and formation of SAHF requires an intact pRB pathway (88,140), hBrm and/or Brg1 might be involved in SAHF assembly, perhaps through deposition of macroH2A.…”
Section: Incorporation Of Other Sahf Componentsmentioning
confidence: 99%
“…Complexes containing BRG1 have been shown to be required for cell cycle control, apoptosis and differentiation in several biological systems (Dunaief et al, 1994;Murphy et al, 1999;Bultman et al, 2000;Reisman et al, 2002;Martens and Winston, 2003;Hendricks et al, 2004;de la Serna et al, 2006). Homozygous knockout mice for the Brg1 gene die during the embryonic stage, whereas heterozygotic survivors are prone to tumors (Bultman et al, 2000;Saha et al, 2006;de la Serna et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous knockout mice for the Brg1 gene die during the embryonic stage, whereas heterozygotic survivors are prone to tumors (Bultman et al, 2000;Saha et al, 2006;de la Serna et al, 2006). BRG1 protein can interact with different proteins involved in regulation of transcription, such as factors involved in myeloid, erythrocyte, lymphocyte, muscle, neural and adipocyte commitment and/or differentiation (Dunaief et al, 1994;Murphy et al, 1999;Bultman et al, 2000;Reisman et al, 2002;Martens and Winston, 2003;Hendricks et al, 2004;Saha et al, 2006;de la Serna et al, 2006). The BRG1 chromatin remodeling protein can associate with numerous chromatin-modifying complexes, including transcription co-activators and corepressors.…”
Section: Introductionmentioning
confidence: 99%